Temperature considerations in non-spherical bubble collapse near a rigid wall. (November 2015) - Beig, Shahaboddin Alahyari; Johnsen, Eric
Abstract: The inertial collapse of cavitation bubbles is known to be capable of damaging its surroundings. While significant attention has been dedicated to investigating the pressures produced by this process, less is known about heating of the surrounding medium, which may be important when collapse occurs near objects whose mechanical properties strongly depend on temperature (e.g., polymers). Using a newly developed computational approach that prevents pressure and temperature errors generated by naively implemented shock- and interface-capturing schemes, we investigate the dynamics of shock-induced collapse of gas bubbles near rigid surfaces. We characterize the temperature fields based on the relevant nondimensional parameters entering the problem. In particular, we show that bubble collapse causes temperature rises in neighboring solid objects via two mechanisms: the shock produced at collapse and heat diffusion from the hot bubble close to the object.